PENGARUH MEDIA MIND MAPPING TERHADAP DAYA INGAT ANAK USIA PRASEKOLAH DI TK NEGERI PEMBINA 3 KOTA PEKANBARU - Riamah Riamah; Anita Syarifah; Awaluddin Awaluddin; Muhammad Irwan; Sari Pratiwi (Jurnal Keperawatan Abdurrab, 2024)
Memory is a person's ability to recall information that has been learned and that has been stored in the brain. Without a strong memory, children will have difficulty receiving information. The purpose of this study was to determine the effect of Mind Mapping Media on Memory in Preschool Age Children at State Kindergarten Pembina 3 Pekanbaru City. Data collection was done using observation sheets. The sample was determined by the Total Sampling method as many as 40 respondents at TK Negeri Pembina 3 Pekanbaru City. This study used a quasy-experimental design with a pre-post test design with one group. The analysis was done by univariate analysis and bivariate analysis using Non-parameric Wilcoxon test. The research was conducted on June 20 - June 22, 2023. Based on the results of csrosstabulation before being given mind mapping media, the results obtained almost entirely moderate memory as many as 19 respondents (47.5%) then after being given mind mapping media, the memory of children is almost entirely high as many as 37 respondents (92.5%). Analysis was carried out by univariate analysis and bivariate analysis using the Wilcoxon Non-parametric test. The statistical test results obtained a p-value of 0.000 <0.005, it can be concluded that there is an effect of Mind Mapping Media on memory in preschool children at State Kindergarten Pembina 3 Pekanbaru City. It is expected that teachers can apply mind mapping media as an alternative learning media to improve children's memory and more often invite children to learn by using pictures.